Long‐term outcome of centrally located low‐grade glioma in children. Issue 14 (26th April 2013) - Terashima, Keita; Chow, Kevin; Jones, Jeremy; Ahern, Charlotte; Jo, Eunji; Ellezam, Benjamin; Paulino, Arnold C.; Okcu, M. Fatih; Su, Jack; Adesina, Adekunle; Mahajan, Anita; Dauser, Robert; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Optimal management of children with centrally located low‐grade glioma (LGG) is unclear. Initial interventions in most children are chemotherapy in younger and radiation therapy (RT) in older children. A better understanding of the inherent risk factors along with the effects of interventions on long‐term outcome can lead to reassessment of the current approaches to minimize long‐term morbidity. METHODS To reassess the current treatment strategies of centrally located LGG, we compared the long‐term survival and morbidity of different treatment regimens. Medical records of patients primarily treated at Texas Children's Cancer and Hematology Centers between 1987 and 2008 were reviewed. RESULTS Forty‐seven patients with a median follow‐up of 79 months were included in the analysis. The 5‐year overall survival and progression‐free survival (PFS) for all patients were 96% and 53%, respectively. The 5‐year PFS for those treated initially with RT (12 patients; median age, 11 years [range, 3‐15 years]) and with chemotherapy (28 patients; median age, 2 years [range 0‐8 years]) were 76% and 37%, respectively (log‐rank test P = .02). Among children who progressed after chemotherapy, the 5‐year PFS after salvage RT was 55%. Patients diagnosed at a younger age (<5 years) were more likely to experience endocrine abnormalities (Fisher exact test; P<.00001). CONCLUSIONS Effective and durable tumor control was obtained with RT as initial treatment. In younger patients, chemotherapy can delay the use of RT; however, frequent progression and long‐term morbidity are common. More effective and less toxic therapies are required in these patients, the majority of whom are long‐term survivors. Cancer 2013;119:2630‐2638. © 2013 American Cancer Society.